Longer duration of obesity is associated with a reduction in urinary angiotensinogen in prepubertal children - Morato, Manuela; Schaefer, Franz (Pediatric nephrology, 2017)
BackgroundWe aimed to study the impact of obesity on urinary excretion of angiotensinogen (U-AGT) in prepubertal children, focusing on the duration of obesity and gender. Also, we aimed to evaluate whether plasma angiotensinogen (P-AGT) and hydrogen peroxide (H2O2) play a role in the putative association.MethodsCross-sectional evaluation of 305 children aged 8-9 years (160 normal weight, 86 overweight, and 59 obese). Anthropometric measurements and 24-h ambulatory blood pressure monitoring were performed. Angiotensinogen (AGT) was determined by a commercial enzyme-linked immunosorbent assay (ELISA) kit and H2O2 by a microplate fluorometric assay.ResultsU-AGT and P-AGT levels were similar across body mass index (BMI) groups and between sexes. However, boys who were overweight/obese since the age of 4 years presented lower levels of U-AGT compared with those of normal weight at the same age. In children who were overweight/obese since the age of 4, urinary H2O2 decreased with P-AGT.ConclusionsA higher duration of obesity was associated with decreased U-AGT in boys, thus reflecting decreased intrarenal activity of the renin-angiotensin system. Also, children with a longer duration of obesity showed an inverse association between urinary H2O2 and P-AGT. Future studies should address whether these results reflect an early compensatory mechanism to limit obesity-triggered renal dysfunction.